2015
DOI: 10.1016/j.ymeth.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of plasma thermograms. Utility, practical approaches and considerations

Abstract: Differential scanning calorimetry (DSC) studies of blood plasma are part of an emerging area of the clinical application of DSC to biofluid analysis. DSC analysis of plasma from healthy individuals and patients with various diseases has revealed changes in the thermal profiles of the major plasma proteins associated with the clinical status of the patient. The sensitivity of DSC to the concentration of proteins, their interactions with other proteins or ligands, or their covalent modifications underlies the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 23 publications
5
66
1
1
Order By: Relevance
“…The thermal profiles of heat capacity changes for aqueous solutions of human blood serum from athletes have been described and discussed in details earlier [37]. Comparing DSC curves of athletes serum diluted with distilled water (pH 6.5-7.0) with curves reported for serum/plasma of healthy persons where the final pH of solutions was in the range 7.2-7.5 [25][26][27][29][30][31][32][33][34][35][36], distinct differences are visible. The main origin of these differences is probably the thermal denaturation profile of fatty acid-free fraction of albumin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal profiles of heat capacity changes for aqueous solutions of human blood serum from athletes have been described and discussed in details earlier [37]. Comparing DSC curves of athletes serum diluted with distilled water (pH 6.5-7.0) with curves reported for serum/plasma of healthy persons where the final pH of solutions was in the range 7.2-7.5 [25][26][27][29][30][31][32][33][34][35][36], distinct differences are visible. The main origin of these differences is probably the thermal denaturation profile of fatty acid-free fraction of albumin.…”
Section: Resultsmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) has recently been found useful in the support of various medical diagnoses [25][26][27][28][29][30][31][32][33][34][35][36] by analysis of plasma or serum heat capacity changes in the temperature range of protein components thermal denaturation. DSC profiles of biofluids are able to reflect their modified composition, changes in thermal stability of major proteome components resulting from covalent modifications or binding interactions involving disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was higher than the control value in the operable patients. Numerous investigators confirmed the significant correlation between the melting or unfolding profile of thermally denatured structures as a disease specific signature (thermogram) of blood plasma components and the neoplastic diseases status [13][14][15][16][17][18][19][23][24][25][26]. Recently, there are continuous research efforts to demonstrate the efficacy of DSC-based analysis and to validate the results making it possible to use in a clinical practice [15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences confirmed that differential scanning calorimetry (DSC) has been successfully applied in a number of clinical studies, where detected and followed different inflammatory and malignant tumorous processes with the examination of blood samples [13][14][15]. These researches have proved that applied method is a noninvasive option for diagnosis and monitoring of patients.…”
Section: Introductionmentioning
confidence: 98%
“…DSC is a technique that is becoming widely used for characterization of disease induced thermodynamic changes in the serum proteome, more precisely of the changes affecting the most abundant serum proteins in a variety of oncological diseases [8,9,12,[26][27][28][29][30][31][32][33][34] and so far only in limited cases for characterization of premalignant states such as monoclonal gammopathy of undetermined significance (MGUS) [35] and soft tissue inflammation [31]. Regarding monoclonal gammopathies, previously we have established that secretory MM (IgG-MM and a small cohort of IgA-MM) sera feature (as a general but not excessive rule) a dramatic reduction in the albumin assigned thermal transition and reciprocal stabilization of the globulins related transition, the latter was attributed to the paraprotein concentration increase [8].…”
Section: Discussionmentioning
confidence: 99%